Capital Intelectual: sua divulgação no setor bancário em Portugal - Silva, Lurdes (2014)
The importance of intangible resources has increased dramatically in recent years comparing to tangible ones. The economy in which we live is the result of competitive pressures that have imposed the implementation of business at an international level as well as a requirement in the application of sophisticated technologies that allow us to follow this fast evolution. In this age of information and innovation organizations will only survive if they are inserted in a global network of strategic relations, generically called as the network economy by Lev (2003). The service sector has stood out against the more traditional sectors of the economy. The intensive use of knowledge and a strong customer orientation created a new reality in today’s organizations: a growing importance attached to innovation, to the quality of products and services offered, to the information and communication technologies adopted, and to the creativity and particular abilities of human resources. The concept of intangible assets is more common in an accounting language and intellectual capital is most often applied in the context of management, being associated with a more comprehensive, multidimensional approach, representing all the knowledge that the institution owns and that it applies in the form of expertise, the creativity and organizational competencies that lead to innovation and to the sustained attainment of future economic benefits. An analysis of the scope of intellectual capital is fundamental to take more appropriate management decisions so that a more appropriate accounting treatment could be given by the accounting standardization organizations. This study intends to analyse the practices of information disclosure of the intellectual capital in the banking sector in Portugal, complementing the analysis of the disclosure of intangible assets in the context of accounting standards with the disclosure of intellectual capital in the context of organizational management. In particular, our main aims are to identify the extent of disclosure of intellectual capital made by banks in Portugal and also to identify the factors that determine such a disclosure. The disclosure in the context of accounting standards will be studied by checking the disclosure of intangible assets through the items listed in the International Accounting Standard 38 developed by the International Accounting Standards Board. The context of management was analysed by means of creating a voluntary disclosure index based on assumptions of the model Intellectus, developed by the Centro de Investigación sobre la Sociedad del Conocimiento – Instituto de Administración de Empresas (CIC-IADE) of the Universidad Autónoma of Madrid, and of the model Intellectual Capital Statement (made in Europe) (InCaS), both promoted by the European Commission and that we have adapted to the banking sector. When analysing the disclosure of intangible assets based on the context of accounting standards and the voluntary disclosure of intellectual capital, this study has tried to raise awareness about the importance of issuing reports on the intellectual capital as an alternative tool to take management decisions in the existing organizations and reflects the transparency and legitimacy that these institutions seek through a more extensive and more detailed information disclosure of their intellectual capital. Based on a complimentarily of economic theories, together with social and political theories, we tried to check the extent, evolution and tendencies of the compulsory disclosure of intangible assets and of the voluntary disclosure of the intellectual capital analysed in the period 2001-2011. Banks characteristics were also analysed in order to deduce those factors that determine or promote a larger disclosure in this sector. Based on these objectives, we adopted a longitudinal approach to explore the extent and the development of the disclosure of intangible assets as well as the factors that have determined it. Furthermore, we sought to assess the impact of the adoption of IAS 38 in the financial statements of the organizations in this sector. The disclosure index created on the basis of the disclosure requirements stated in IAS 38 from IASB was applied to the consolidated financial statements of the seventeen banks that rendered their statements in Portugal from 2001 to 2009. Since the information disclosed in the context of accounting standards may not have an important role as a management tool once it was not able to reflect what really contributes to the competitiveness and organizational growth, the voluntary disclosure of the intellectual capital was analysed according to the information obtained from the 2010 annual individual reports of the banks operating in Portugal in that year and from their respective websites in 2011. We tried to analyse the extent of the voluntary disclosure of the intellectual capital and of each of its components, human capital, structural capital and relational capital. The comparative analysis of their annual reports and their web pages allowed us to assess the incidence of the disclosure and discover what channel the banking sector focuses on when disclosing their intellectual capital. Also in this analysis the study of the disclosure determinants has allowed us to conclude about the influence of particular characteristics in the voluntary disclosure of the intellectual capital. The results of the analysis to the extent of the disclosure of intangible assets in the consolidated financial statements of the banking groups in Portugal in the period 2001-2009 have shown an average information disclosure of 0.24. This information disclosure evolved from an average value of 0.1940 in 2001 to 0.2778 in 2009. The average value is 0.8286 if it is only considered the disclosure of the intangible assets that the banks possessed. The evolution of this index means an increase in the average disclosure from 0.7852 in 2001 to 0.8788 in 2009. From the first results that are related to the extent of the disclosure of intangible assets in the financial statements, we can verify that the banking groups present a low disclosure level of these resources. However, when considering the disclosure of only the intangible assets that each institution owns, the disclosure level appears to be in compliance with the disclosure requirements for this sector. An evolution in the disclosure of intangible assets for the period considered was confirmed, showing an increase in the information disclosure of intangible assets in 2005, the year in which the accounting rules for intangible assets changed. The analysis that focused on the disclosure in the context of management tried to understand the extent, the incidence and the determinants of the voluntary information disclosure of intellectual capital in the annual reports of 2010 and on their web pages in 2011, studying the 32 banks operating in Portugal in this period. The average voluntary disclosure of the intellectual capital in the 2010 annual reports is 0.4342 while that in web pages is 0.2907. A review of the components of the intellectual capital allowed us to assess the importance that the banks confer to each of these components. The data obtained show that the relational capital, and more specifically the business capital, is the most disclosed component by banks in Portugal both in the annual reports and in their institutional web pages, followed by the structural capital and, finally, by the human capital. The disclosure of the human capital and the structural capital is higher in the annual reports than that in the websites, while the relational capital is more disclosed in the websites than in the annual reports. The results have also shown that the banks make a complementary use of both sources when disclosing information about their structural capital and relational capital but they do not show any information about their human capital in their websites. We tried to prove the influence of factors that could determine the accounting disclosure and the voluntary disclosure of the intellectual capital in this sector. The change in the IASB accounting rules as from January 1st 2005 gave a greater disclosure of accounting information of intangible assets in the financial statements of banks. The bank size and corporate governance measures have statistically proved to have an influence on the extent of the accounting disclosure of intangible assets and on the voluntary disclosure of the intellectual capital. Economic and financial variables such as profitability, operating efficiency or solvency were not determinants of information disclosure. The instability that the banking sector has experienced in economic and financial indicators in recent years as a result of the global financial markets imbalance has worsen indicators such as profitability, efficiency and solvency and caused major discrepancies in the economic situation between banks in Portugal. This empirical analysis has contributed to confront the disclosure required by accounting rules performed in the financial statements of organizations with that performed in the main disclosure media which is available for entities and which is increasingly requested in the process of taking management decisions. It also allowed us to verify whether there is homogeneity between institutions in the fulfilment of the requirements for information disclosure of intangible assets. However, as for voluntary disclosure of intellectual capital, there are large disparities in the disclosure extent between organizations. Regardless of this sector specific characteristics, the voluntary disclosure of intellectual capital made by banks in Portugal follows the trends in other sectors and the practices adopted in other countries, namely regarding the amount of information disclosed, the incidence of the disclosure on the indicators of relational capital and the importance of variables such as size as determinants of disclosure of intellectual capital. For a further knowledge in this field, we created a specific index for the banking sector, considering appropriate indicators for an incisive, comprehensive analysis in order to consider the most relevant indicators of intellectual capital components. Besides, confronting the analysis of disclosure in the context of accounting standards with the study of voluntary disclosure brought a new analysis approach to the research on intellectual capital disclosure. With this study, we have also intended to raise greater awareness of the need for harmonization in the intellectual capital disclosure on the part of the regulatory banking authority by means of a demanding, consistent and transparent report of intellectual capital with simple, clear, objective indicators so that those interested in disclosing intellectual capital information in the organizations in this sector may obtain more harmonized and comparable information. A research on the disclosure quality of intellectual capital, together with the application of other analysis methodologies in this sector, might be a promising approach for future research. Applying the voluntary disclosure index to the same sector in other countries may also contribute to the knowledge of disclosure practices in different geographical environments. We highlight the relevance of further studies contributing to the harmonization and consistency in the presentation of an intellectual capital report so as to enable organizations to disclose the resources that contribute most to their competitiveness and growth.